Optical solitons for Kundu-Mukherjee-Naskar equation via enhanced modified extended tanh method - Cakicioglu, Hasan; Cinar, Melih; Secer, Aydin; Bayram, Mustafa (SPRINGER, 2023)
This article investigates the optical soliton solutions of the Kundu-Mukherjee-Naskar (KMN) equation with the help of the enhanced modified extended tanh method (eMETEM). The equation is crucial for simulating the bending of light beam, rogue waves in the seas, and fiber pulses in optics. Some different kinds of solitons such as singular-periodic, dark and singular for the KMN equation have been successfully obtained by the used method. Utilizing Maple, we confirm that all acquired solutions satisfy the considered equation. We have also analyzed the impact of the parameters graphically in the considered equation. The results shown in the figures reveal that the parameters of the considered equation have an important effect upon soliton dynamics. It is anticipated that the gained solutions and used approach would create remarkable chances for future work in a variety of science areas.
Keywords: Optical fiber; Analytical technique; Chromatic dispersion; Soliton dynamic; Analytical solutions; GINZBURG-LANDAU EQUATION; FOKAS-LENELLS EQUATION; PERTURBATION; Engineering; Physics; Optics